The two single-strand cleavages at each end of Tn10 occur in a specific order during transposition. - Bolland, S (1995)
During Tn10 transposition, the element is excised from the donor site by double-strand cleavages at the two transposon ends. Double-strand cleavage is a central step in the nonreplicative transposition reaction of many transposons in both prokaryotes and eukaryotes. Evidence is presented to show that the Tn10 double-strand cut is made by an ordered, sequential cleavage of the two strands. The transferred strand is cut first, and then the nontransferred strand is cleaved. The single-strand nicked intermediate is seen to accumulate when Mn2+ is substituted for Mg2+ in the reaction or when certain mutant transposases are used. The fact that the transferred strand is cleaved before the non-transferred strand implies that the order of strand cleavages is not the determining factor that precludes a replicative mechanism of transposition.